A randomized controlled trial of an intervention for infants' behavioral sleep problems. Issue 1 (December 2015) - Hall, Wendy; Hutton, Eileen; Brant, Rollin; Collet, Jean; Gregg, Kathy; Saunders, Roy; Ipsiroglu, Osman; Gafni, Amiram; Triolet, Kathy; Tse, Lillian; Bhagat, Radhika; Wooldridge, Joanne
Abstract Background Infant behavioral sleep problems are common, with potential negative consequences. We conducted a randomized controlled trial to assess effects of a sleep intervention comprising a two-hour group teaching session and four support calls over 2 weeks. Our primary outcomes were reduced numbers of nightly wakes or parent report of sleep problem severity. Secondary outcomes included improvement in parental depression, fatigue, sleep, and parent cognitions about infant sleep. Methods Two hundred thirty five families of six-to-eight month-old infants were randomly allocated to intervention (n = 117) or to control teaching sessions (n = 118) where parents received instruction on infant safety. Outcome measures were observed at baseline and at 6 weeks post intervention. Nightly observation was based on actigraphy and sleep diaries over six days. Secondary outcomes were derived from the Multidimensional Assessment of Fatigue Scale, Center for Epidemiologic Studies Depression Measure, Pittsburgh Sleep Quality Index, and Maternal (parental) Cognitions about Infant Sleep Questionnaire. Results One hundred eight intervention and 107 control families provided six-week follow-up information with complete actigraphy data for 96 in each group: 96.9 % of intervention and 97.9 % of control infants had an average of 2 or more nightly wakes, a risk difference of −0.2 % (95 % CI: −1.32, 0.91). 4 % of intervention and 14 % of control infants had parent-assessed severe sleep problems: relative risk 0.3, a risk difference of −10 % (CI: 0.11, 0.84-16.8 to −2.2). Relative to controls, intervention parents reported improved baseline-adjusted parental depression (CI: −3.7 to −0.4), fatigue (CI: −5.74 to −1.68), sleep quality (CI: −1.5 to −0.2), and sleep cognitions: doubts (CI: −2.0 to −0.6), feeding (CI: − 2.1 to - 0.7), anger (CI: − 1.8 to - 0.4) and setting limits (CI: −3.5 to −1.5). Conclusions The intervention improved caregivers' assessments of infant sleep problem severity and parental depression, fatigue, sleep, and sleep cognitions compared with controls. Trial registration ISRCTN42169337, NCT00877162